2019
DOI: 10.1002/acm2.12653
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological impacts of collimator‐scattered protons in spot‐scanning proton therapy

Abstract: To improve the penumbra of low‐energy beams used in spot‐scanning proton therapy, various collimation systems have been proposed and used in clinics. In this paper, focused on patient‐specific brass collimators, the collimator‐scattered protons' physical and biological effects were investigated. The Geant4 Monte Carlo code was used to model the collimators mounted on the scanning nozzle of the Hokkaido University Hospital. A systematic survey was performed in water phantom with various‐sized rectangular target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This trend was also supported by experimental results, which showed an increase of 1.5 keV μm −1 in LET F in water further away from the field edge. Although no comparison was made with uncollimated fields, Ueno et al also showed through MC simulations that the LET D of collimator-scattered protons was several keV μm −1 higher than that of unscattered ones, in a set of investigated positions (Ueno et al 2019). The reported increase is also in agreement with the results found in this work in terms of LET D , although a direct comparison cannot be made given the differences in the irradiated fields, scored quantities and positions.…”
Section: Discussionsupporting
confidence: 81%
“…This trend was also supported by experimental results, which showed an increase of 1.5 keV μm −1 in LET F in water further away from the field edge. Although no comparison was made with uncollimated fields, Ueno et al also showed through MC simulations that the LET D of collimator-scattered protons was several keV μm −1 higher than that of unscattered ones, in a set of investigated positions (Ueno et al 2019). The reported increase is also in agreement with the results found in this work in terms of LET D , although a direct comparison cannot be made given the differences in the irradiated fields, scored quantities and positions.…”
Section: Discussionsupporting
confidence: 81%
“…A slightly increased dose averaged LET of the protons scattered at the aperture could be detected by Ueno et al 35 Although the increased LET was negligible in the overall LET, it should be considered especially for the application with small fields. These secondary effects contributing to absorbed dose require particular emphasis in subsequent works.…”
Section: Discussionmentioning
confidence: 90%
“…RayStation TPS accurately predicted the dose bump as well as lateral penumbra. Ueno et al 18 reported the maximum dose increase of 22% for all the tested condition from collimator‐scattered protons. This result was consistent with our finding that maximum surface dose increased by AA scattered protons of 25%.…”
Section: Discussionmentioning
confidence: 94%
“…A Monte Carlo simulation study of the lateral penumbra of a PBS proton system was conducted by Winterhalter et al 17 They studied various beam conditions and recommended that the collimated edge enhancement with variable preabsorber be an optimal way to reduce the lateral fall‐off for the PBS proton therapy system. Ueno et al 18 conducted a Monte Carlo simulation of the impact of collimator‐scattered protons in PBS proton therapy. They reported increased surface dose by 3.0–22.0% due to collimator‐scattered protons.…”
Section: Introductionmentioning
confidence: 99%